2018
DOI: 10.3389/fimmu.2018.01140
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin Assemblies in Virus Infection

Abstract: Tetraspanins (Tspans) are a family of four-span transmembrane proteins, known as plasma membrane “master organizers.” They form Tspan-enriched microdomains (TEMs or TERMs) through lateral association with one another and other membrane proteins. If multiple microdomains associate with each other, larger platforms can form. For infection, viruses interact with multiple cell surface components, including receptors, activating proteases, and signaling molecules. It appears that Tspans, such as CD151, CD82, CD81, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 128 publications
2
92
0
Order By: Relevance
“…This is in line with studies having shown that in contrast to hepatocytes, other cell types which are not susceptible to HCV express distinct CD81 partners that restrict HCV entry [114][115][116]. Interestingly, tetraspanin assemblies are emerging as key platforms regulating the entry of unrelated viruses [117][118][119].…”
Section: The Regulatory Role Of Cd81-tetraspanin Platformssupporting
confidence: 82%
“…This is in line with studies having shown that in contrast to hepatocytes, other cell types which are not susceptible to HCV express distinct CD81 partners that restrict HCV entry [114][115][116]. Interestingly, tetraspanin assemblies are emerging as key platforms regulating the entry of unrelated viruses [117][118][119].…”
Section: The Regulatory Role Of Cd81-tetraspanin Platformssupporting
confidence: 82%
“…In the context of host-pathogen interaction, CD9enriched microdomains have been described as important host cell factors in infections by various viruses [24]. Likewise, our comparative analyses on the function of different tetraspanins and tetraspanin domains implicated a crucial role of CD9 in HPV16 infection of HeLa cells [19].…”
Section: Introductionmentioning
confidence: 57%
“…These molecules are announced as plasma membrane "master organizers" due to their ability to interact with multiple plasma membrane molecules and to form functional tetraspanin-enriched microdomains [21][22][23]. From the 33 tetraspanins identified in humans so far, only a portion has been shown to play an important role in regulating the entry process of various viruses including CD9, CD63, CD81 and CD151 [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Here, HPV particles associate with large CD151 patches to which they remain bound to, until they co-internalize with them 4,5 . Additionally, HPVs associate with aggregates of other tetraspanins 3,6 and several other viruses colocalize with tetraspanin patches or use tetraspanin assemblies for cell entry as well [7][8][9] . These observations lead to the proposal that virus contact with the cell membrane triggers the formation of tetraspanin-based virus entry platforms 6 .…”
Section: Anatomy Of a Viral Entry Platform Differentially Functionalimentioning
confidence: 99%
“…Additionally, HPVs associate with aggregates of other tetraspanins 3,6 and several other viruses colocalize with tetraspanin patches or use tetraspanin assemblies for cell entry as well [7][8][9] . These observations lead to the proposal that virus contact with the cell membrane triggers the formation of tetraspanin-based virus entry platforms 6 . Such viral entry platforms would require at least two functionalities: attachment and internalization of the virus.…”
Section: Anatomy Of a Viral Entry Platform Differentially Functionalimentioning
confidence: 99%